2015
DOI: 10.1039/c4bm00278d
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of a novel anticancer compound anisomelic acid using chitosan-coated porous silica nanorods for enhancing the apoptotic effect

Abstract: Targeted delivery of a novel anticancer compound anisomelic acid using chitosan-coated porous silica nanorods for enhancing the apoptotic effect, 2015, BIOMATERIALS SCIENCE, (3) Targeted cancer therapies are currently a strong focus in biomedical research. The most common approach is to use nanocarrier-based targeting to specifically deliver conventional anticancer drugs to enhance their therapeutic efficacy, increase bioavailabil ity, and decrease the side-effects on normal cells. A step further towards highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…29 The size distributions of MSPs were obtained by performing detail statistical analysis of TEM images for MSP1, MSP2 and MSP4 samples as presented in Fig. 1.…”
Section: Characterization Of Msps and Release Of Ag + From Mspsmentioning
confidence: 99%
“…29 The size distributions of MSPs were obtained by performing detail statistical analysis of TEM images for MSP1, MSP2 and MSP4 samples as presented in Fig. 1.…”
Section: Characterization Of Msps and Release Of Ag + From Mspsmentioning
confidence: 99%
“…Poly(dimethylaminoethyl methacrylate)-poly(butylmethacrylate) polymeric micelles transfected COS-7 and OVCAR-3 cells efficiently with minor toxicity (Funhoff et al 2005). Folate-targeted chitosan NPs intracellular delivery was more target specific than non targeted ones (Senthilkumar et al 2015). In another Karmali et al (2009) study, folate-conjugated chitosan NPs showed greater cytotoxicity and uptake in folate receptor expressing cells (Song et al 2013).…”
Section: Targeted Drug Deliverymentioning
confidence: 97%
“…(Li and Huang, 2008) We have to date shown that our developed MSN platform can be functionalized for cancer cell specific internalization and is suitable for targeted delivery of hydrophobic compounds including commercially available anticancer drugs, (Mamaeva et al, 2011; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 5 Niemelä et al, 2015;Senthilkumar et al, 2015;Wittig et al, 2014) for which the release of cargo has been mainly confined to the intracellular environment. (Lu et al, 2007) In vivo we have shown that the carrier can be intravenously, locally and orally administered, accumulates in tumor tissue, lacks cytotoxic side-effects, is biodegradable and most likely eliminated through renal excretion after intravenous administration.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Our nanocarrier system has already previously been comprehensively evaluated for cytotoxicity, proven non-cytotoxic and biocompatible, (Desai et al, 2016;Mamaeva et al, 2011;Rosenholm et al, 2009a;Senthilkumar et al, 2015;Wittig et al, 2014) and was thus A C C E P T E D M A N U S C R I P T…”
Section: Intracellular Delivery and Dye Releasementioning
confidence: 99%